2011
DOI: 10.1038/ejhg.2011.136
|View full text |Cite
|
Sign up to set email alerts
|

Discrepancies in reporting the CAG repeat lengths for Huntington's disease

Abstract: on behalf of the European Huntington's Disease Network Huntington's disease results from a CAG repeat expansion within the Huntingtin gene; this is measured routinely in diagnostic laboratories. The European Huntington's Disease Network REGISTRY project centrally measures CAG repeat lengths on fresh samples; these were compared with the original results from 121 laboratories across 15 countries. We report on 1326 duplicate results; a discrepancy in reporting the upper allele occurred in 51% of cases, this redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 9 publications
(9 reference statements)
1
6
0
Order By: Relevance
“…Potential variations in CAG numbers between laboratories may be a limitation of such a multicentre survey, but this is a common finding, as demonstrated in a systematic comparative analysis in the European Huntington's Disease Network [37], and the similarity of our data confirms the general validity of our interpretation. The low number of intermediate and low penetrance CAG range does not allow firm conclusions about the phenotype in this group.…”
Section: Discussionsupporting
confidence: 81%
“…Potential variations in CAG numbers between laboratories may be a limitation of such a multicentre survey, but this is a common finding, as demonstrated in a systematic comparative analysis in the European Huntington's Disease Network [37], and the similarity of our data confirms the general validity of our interpretation. The low number of intermediate and low penetrance CAG range does not allow firm conclusions about the phenotype in this group.…”
Section: Discussionsupporting
confidence: 81%
“…Fragment analysis, as well as Southern blotting and TP‐PCR, is dependent upon accurate amplification and fragment sizing and does not analyze the DNA sequence itself. Studies have shown that in clinical HD analysis, 3%–13% of alleles fall outside error limits set by generally adapted best practice guidelines (Losekoot et al., ; Quarrell et al., ). An exact determination of the repeat count is important for clinical diagnostics of HD patients, in particular for the cases where repeat sizes cross borders of the repeat size ranges correlated with disease phenotypes.…”
Section: Introductionmentioning
confidence: 99%
“…Alleles up to 26 repeats are considered normal, while 27–35 repeats are intermediate alleles with potential to expand into the disease range in the next generation. Alleles with 36–39 CAG repeats are HD‐causing alleles with reduced penetrance, and the patient may or may not develop HD, and while alleles with ≥40 repeats are full‐penetrance HD‐causing alleles (Losekoot et al., ; Palomaki & Richards, ; Quarrell et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Once we have more specific information regarding the factors that impact phenotype expression in the IA and RP ranges, it might become increasingly important to more accurately report the length of a person’s longest CAG repeat allele. Little attention is given in the literature to the issue of inconsistent reporting of CAG repeat lengths, which occurs in up to 51% of tests [33]. The ACMG/ASHG guidelines state that acceptable error rates for CAG repeat lengths is ± 2 repeats for alleles with less than 50 repeats [3].…”
Section: Discussionmentioning
confidence: 99%